2013
DOI: 10.1371/journal.pone.0057510
|View full text |Cite
|
Sign up to set email alerts
|

Double Trouble: Does Co-Morbid Chronic Somatic Illness Increase Risk for Recurrence in Depression? A Systematic Review

Abstract: ObjectiveTo perform a systematic review, and if possible a meta-analysis, to establish whether depressed patients with co-morbid chronic somatic illnesses are a high risk “double trouble” group for depressive recurrence.MethodThe databases PubMed, EMbase and PsycINFO were systematically searched until the 4th of December 2012 by using MeSH and free text terms. Additionally, reference lists of retrieved publications and treatment guidelines were reviewed, and experts were consulted. Inclusion criteria were: dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
(34 reference statements)
0
11
1
2
Order By: Relevance
“…In that study, investigation of a younger adult population (aged 18-65 years) showed that musculoskeletal diseases and diabetes had a negative impact on the course of depression at 2-year followup; however, there was no impact of overall somatic disease burden on the course of depression (Gerrits et al, 2013). In contrast to our findings, a recent review found no higher risk for recurrence of depression in the presence of somatic comorbidity (Kok et al, 2013). However, the results of that review should be interpreted with caution as only a few studies were included because most of them examined recurrence of depression in a somatically ill population only.…”
Section: Discussioncontrasting
confidence: 99%
“…In that study, investigation of a younger adult population (aged 18-65 years) showed that musculoskeletal diseases and diabetes had a negative impact on the course of depression at 2-year followup; however, there was no impact of overall somatic disease burden on the course of depression (Gerrits et al, 2013). In contrast to our findings, a recent review found no higher risk for recurrence of depression in the presence of somatic comorbidity (Kok et al, 2013). However, the results of that review should be interpreted with caution as only a few studies were included because most of them examined recurrence of depression in a somatically ill population only.…”
Section: Discussioncontrasting
confidence: 99%
“…That is, the very process of going through an episode of depression produces a change in underlying causal factors that increase the risk of having future episodes. Possible causal mechanisms underlying the scarring hypothesis have been described for biological factors, such as genetics (Lok et al, 2013), the HPA axis (Lok et al, 2012), cognitive factors (implicit and explicit cognitive factors, Elgersma, Glashouwer, Bockting, Penninx, & de Jong, 2013) and stress-related factors (Beshai, Dobson, Bockting, & Quigley, 2011;Kok et al, 2013;Lok et al, 2013;Teasdale et al, 2000). This area is ripe for more rigorous tests.…”
Section: Recurrencementioning
confidence: 99%
“…Physical health, particularly self-rated health (SRH), chronic medical conditions (CMC), and activities of daily living (ADL), are associated with polypharmacy and depression [19][20][21]. Polypharmacy is also a consequence of being diagnosed with multiple conditions [6,7,10,18].…”
Section: Introductionmentioning
confidence: 99%
“…This means that these health indicators are strong determinants and correlates of polypharmacy [6,7,10,18]. Poor physical health (CMC, SRH, and ADL) and depressive symptomatology also have bidirectional associations [19][20][21]. As a result, there is a need to control for physical health (e.g., CMC, SRH, and ADL) in the studies that wish to understand the association between polypharmacy and depressive symptoms [6,7,10,18].…”
Section: Introductionmentioning
confidence: 99%